Investment Opportunities and Risks in Frontier Equity Markets: A Case of the Nairobi Securities Exchange - Limo, Rose Jepkorir/RL (2013)
The misunderstood frontier markets universally known for their hidden dangers may be the only international diversification alternative option left today, to liberate global investors at a time when the world equity markets have simply been displaying disappointing performance. Over the past few years, these markets have increasingly gained attention from investors worldwide for the potential international diversification benefits that these markets offer in terms of reduction in total portfolio risk and consequently improving portfolio returns. Using daily data from 1 July 1998 to 30 June 2013, this paper investigates the correlation and integration of the Nairobi Securities Exchange (NSE) with world markets. The correlation and regression results reveal that the NSE and individual frontier market countries exhibit low levels of correlation with developed and emerging markets as well as minimal exposure to the global factor. In contrast, developed and emerging markets exhibit an increased level of integration whereas the NSE offers no indication of increased integration over time. Furthermore, the NSE has low to moderate frontier intra-market correlations. This paper finds strong achievable diversification benefits by including the NSE equities in an international portfolio. Despite this finding, it emerges that global investors continue to shy away from investing in frontier markets.